Indian monsoon wind variability since ~11 kyr in the northwestern and northeastern Arabian Sea. (15th September 2021) - Ravichandran, Muthusamy; Gupta, Anil K.; Mohan, Kuppusamy; Lakshumanan, Chokkalingam
Graphical abstract: Highlights: We studied varying monsoon wind stress in the Arabian Sea during the Holocene. Surface productivity was high during the early Holocene. Summer monsoon was weak and winter monsoon was strong in the middle Holocene. Monsoon winds show high spatial variability in strength in the Arabian Sea. Abstract: In this paper, we use planktic foraminifera and mixed-layer species from cores SK-240/327, SK-243/I- and ABP-25/03, northeastern Arabian Sea to investigate monsoon wind variability. Planktic foraminifera include Globigerina bulloides, a monsoon proxy and mixed-layer species Globigerinoides ruber, Gs. sacculifer, Gs. obliquus and Gs. extremus from cores SK-240/327, SK-243/I-1 and ABP-25/03 encompassing last ~11 calibrated kilo years before the Present (~11 cal kyr BP). The population abundances of Globigerina bulloides and mixed-layer species were compared with published Globigerina bulloides percentages from the western Arabian Sea Ocean Drilling Program Holes 723A, 724B and 727B, and eastern Arabian Sea core ABP-25, 02 to understand variations in Indian monsoon winds during the Holocene. In the eastern Arabian Sea, upwelling induced productivity was higher during 10–6.5 cal kyr BP which decreased during 6.5–3 cal kyr BP. In the northwestern Arabian Sea, we observe a similar scenario but not every site captured this change owing to spatial diverseness in monsoon wind stress. The productivity increased since 3 cal kyr BP due to intense summer monsoon winds in the northeastern Arabian Sea, whereas productivity began to increase at ~1.5 cal kyr BP in the northwestern Arabian Sea. The upwelling intensity shows large spatial and temporal variations in the eastern and western Arabian Sea, indicating varying monsoon wind strength across the Arabian Sea during the Holocene. The spectral analysis performed on Globigerina bulloides shows cyclicity which is associated with solar variability during the past 11 kyr record in the northeastern Arabian Sea.